The acute impact of polyphenols from Hibiscus sabdariffa in metabolic homeostasis: an approach combining metabolomics and gene-expression analyses1. Issue 9 (2nd September 2015) - Beltrán-Debón, Raúl; Rodríguez-Gallego, Esther; Fernández-Arroyo, Salvador; Senan-Campos, Oriol; Massucci, Francesco A.; Hernández-Aguilera, Anna; Sales-Pardo, Marta; Guimerà, Roger; Camps, Jordi; Menendez, Javier A.; Joven, Jorge
<x xml:space="preserve">Abstract</x> The acute multifunctional effects of polyphenols in humans.